Reproductive isolation in a nascent species pair is associated with aneuploidy in hybrid offspring - Dion-Côté, Anne-Marie; Symonová, Radka; Ráb, Petr; Bernatchez, Louis (Proceedings - Royal Society. Biological sciences, 2015)
Speciation may occur when the genomes of two populations accumulate genetic incompatibilities and/or chromosomal rearrangements that prevent inter-breeding in nature. Chromosome stability is critical for survival and faithful transmission of the genome, and hybridization can compromise this. However, the role of chromosomal stability on hybrid incompatibilities has rarely been tested in recently diverged populations. Here, we test for chromosomal instability in hybrids between nascent species, the 'dwarf' and 'normal' lake whitefish (Coregonus clupeaformis). We examined chromosomes in pure embryos, and healthy and malformed backcross embryos. While pure individuals displayed chromosome numbers corresponding to the expected diploid number (2n = 80), healthy backcrosses showed evidence of mitotic instability through an increased variance of chromosome numbers within an individual. In malformed backcrosses, extensive aneuploidy corresponding to multiples of the haploid number (1n = 40, 2n = 80, 3n = 120) was found, suggesting meiotic breakdown in their F1 parent. However, no detectable chromosome rearrangements between parental forms were identified. Genomic instability through aneuploidy thus appears to contribute to reproductive isolation between dwarf and normal lake whitefish, despite their very recent divergence (approx. 15-20 000 generations). Our data suggest that genetic incompatibilities may accumulate early during speciation and limit hybridization between nascent species.
Keywords: embryo nesavčí; Reproduction; chromozomální nestabilita; vznik druhů (genetika); rozmnožování; Reproductive Isolation; Embryo, Nonmammalian; Salmonidae; Hybridization, Genetic; Female; Chromosomal Instability; zvířata; hybridizace genetická; ženské pohlaví; Male; reprodukční izolace; Genetic Speciation; aneuploidie; Animals; mužské pohlaví; Aneuploidy